Penggunaan Media Sosial Oleh Para Individual Via Smart Phones - Hans Christian Marwi (Fakultas Teknologi Informasi, Universitas Atma Jaya Makassar, 2020)
Nowadays smart phones are essential part in people’s life. People mainly use them to access social media with Facebook as the most visited web site. Many organizations take advantage by promoting their products on Facebook by creating their organization’s page or by joining merchant groups. Nevertheless, the organizations commonly work in bussiness hours, while users/customers access their smart phones almost everytime (day and night). In addition, many organizations do not provide dedicated staff to maintain their bussiness on line. This paper study about people behaviour while they access social media and perform on line transactions.